2014
DOI: 10.1007/s11738-014-1681-y
|View full text |Cite
|
Sign up to set email alerts
|

The natural alkaloid sanguinarine promotes the expression of heat shock protein genes in Arabidopsis

Abstract: Small-molecule heat shock response inducers are known to enhance heat tolerance in plants. In this paper, we report that a plant alkaloid enhances the heat tolerance of Arabidopsis. We investigated 12 commercially available alkaloids to determine whether they enhance the heat tolerance of Arabidopsis seedlings by using an in vitro assay system with geldanamycin, which is a known heat shock response inducer, as a positive control. Accordingly we found that the isoquinoline alkaloid sanguinarine can enhance heat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…sesamin and kobusin), and alkaloids (e.g. sanguinarine, berberin, aristolochic acid, and narciclasine; Bailey, 1970;Trifunovic et al, 2003;Ono et al, 2006;Evidente et al, 1983;Gardiner et al, 2008;Na et al, 2011;Hu et al, 2012;Nakagawa et al, 2012;Hara and Kurita, 2014). Interestingly, the bioactivity of berberin and coptisin has been linked to the dioxole group as a structural analog, but without this functional group (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…sesamin and kobusin), and alkaloids (e.g. sanguinarine, berberin, aristolochic acid, and narciclasine; Bailey, 1970;Trifunovic et al, 2003;Ono et al, 2006;Evidente et al, 1983;Gardiner et al, 2008;Na et al, 2011;Hu et al, 2012;Nakagawa et al, 2012;Hara and Kurita, 2014). Interestingly, the bioactivity of berberin and coptisin has been linked to the dioxole group as a structural analog, but without this functional group (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…We used the promoter of a small HSP gene, i.e., the HSP17.6C-CI (At1g53540) gene of Arabidopsis. A previous study reported that the HSP17.6C-CI gene was upregulated by the addition of GDA (Hara and Kurita, 2014). The upstream region (1 kb) of the HSP17.6C-CI gene was inserted into the site adjacent to the b -glucuronidase (GUS) reporter gene, which was followed by the heat shock protein terminator.…”
Section: Resultsmentioning
confidence: 99%
“…Natural compounds have been reported to exert inducing effects on the HSR in plants. It has been demonstrated that the application of salicylic acid (SA) (Dat et al, 1998), geldanamycin (GDA) (Yamada et al, 2007), sanguinarine (Hara and Kurita, 2014), and (E)-2-hexenal and its related compounds (Yamauchi et al, 2015) have been shown to induce the expression of plant HSP genes and enhance the heat tolerance of plants. In Arabidopsis, the HSP17.6C-CI (At1g53540) gene which belongs to the small HSP family was highly upregulated by sanguinarine (Hara and Kurita, 2014) and (E)-2-hexenal (Yamauchi et al, 2015), suggesting that this gene is a common regulon controlled by chemical HSR inducers in Arabidopsis.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the effects of alkaloid on Arabidopsis and rapeseed seedlings, WT plants of Arabidopsis were firstly grown under the same conditions as above. Before the freezing treatment, a dosage of 0, 10, and 30 nmol alkaloid (atropine) per seedling was added to the soil for Arabidopsis, while a dosage of 0, 50, and 150 nmol per seedling was added to the soil for rapeseed accession Zhongshuang 11 (ZS11) according to the previous study (Hara and Kurita, 2014). After inoculation overnight, the 21-d-old Arabidopsis plants were transferred into a growth chamber at −4°C for 4 h, the three-leaf-stage rapeseed plants were transferred into the growth chamber at −4°C for 4 h (Yan et al, 2019).…”
Section: Growth Conditions and Stress Treatmentsmentioning
confidence: 99%
“…However, few studies have recognized the positive correlations between alkaloids and stress resistance. Application of sanguinarine for Arabidopsis seedlings under heat stress condition could markedly enhance the tolerance, which presumably by promoting the expression of heat shock proteins like HSP70 and HSP90.1S (Hara and Kurita, 2014;Matsuoka et al, 2016). BnTR1 is predicted to encode a tropinone reductase, which is involved in the metabolic pathway of atropine alkaloids.…”
Section: Protective Role Of Alkaloids Under Lt Conditionsmentioning
confidence: 99%